Economy of scale for green hydrogen-derived fuel production in Nepal - Thapa, Biraj Singh; Pandey, Bishnu; Ghimire, Rahul (Frontiers in Chemistry, 2024)
Opportunity for future green hydrogen development in Nepal comes with end-use infrastructural challenges. The heavy reliance of industries on fossil fuels (63.4%) despite the abundance of hydroelectricity poses an additional challenge to the green transition of Nepal. The presented work aims to study the possibility of storing and utilizing spilled hydroelectricity due to runoff rivers as a compatible alternative to imported petroleum fuels. This is achieved by converting green hydrogen from water electrolysis and carbon dioxide from carbon capture of hard-to-abate industries into synthetic methane for heating applications via the Sabatier process. An economy-of-scale study was conducted to identify the optimal scale for the reference case (Industries in Makwanpur District Nepal) for establishing the Synthetic Natural Gas (SNG) production industry. The techno-economic assessment was carried out for pilot scale and reference scale production unit individually. Uncertainty and sensitivity analyses were performed to study the project profitability and the sensitivity of the parameters influencing the feasibility of the production plant. The reference scale for the production of Synthetic Natural Gas was determined to be 40 Tons Per Day (TPD), with a total capital investment of around 72.15 Million USD. Electricity was identified as the most sensitive parameter affecting the levelized cost of production (LCOP). The 40 TPD plant was found to be price competitive to LPG when electricity price is subsidized below 3.55 NPR/unit (2.7c/unit) from 12 NPR/unit (9.2c/unit). In the case of the 2 TPD plant, for it to be profitable, the price of electricity must be subsidized to well below 2 NPR/kWh. The study concludes that the possibility of SNG production in Nepal is profitable and price-competitive at large scales and at the same time limited by the low round efficiency due to conversion losses. Additionally, it was observed that highly favorable conditions driven by government policies would be required for the pilot-scale SNG project to be feasible.